Penentuan Prioritas Pemilihan Saham LQ45 Dengan Metode Taguchi Loss Function - , Agnadi Kusnowo ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Jakarta Composite Index (JCI) continued rising since Indonesia passed from the monetary crisis in 1997-1999 and reach its peak in early 2008. JCI plunged to the lowest point in November 2010 when the economic crisis hit USA and Europe in 2008. Then JCI continued to rebound until the thesis was written in May 2011. In 2010 JCI provided return in the amount of 46.13%, while the highest return of LQ45 stock showed by KLBF reaching up to 150%. This thesis undertakes to find another LQ45 stocks which have similar characteristics with KLBF stock as a target of investments to get high return. The research is conducted by comparing performance amongst LQ45 stocks through comparison ratios from financial statements in 2010 LQ45. Then undertakes prioritizing selection on LQ45 stock by Taguchi Loss Function method. The first step is investigating to find out what are the significant financial ratios influencing LQ45 stock return. The ratios are Earning Per Share (EPS), Price to Earning Ratio (PER), Book Value (BV), Price to Book Ratio (PBV), Return on Assets (ROA), Return on Equity (ROE), Debt to Equity Ratio (DER), Net Profit Margin (NPM), and Operating Profit Margin (OPM). The data of financial ratios and LQ45 stock return used in earlier research are using financial reports from 2008 until 2010. The results founded that the ratios of the most influential on the LQ45 stock return are PBV and ROA. Then by using KLBFâs PBV and ROA we can selected prioritizing selection on another LQ45 stocks by Taguchi Loss Function method. Taguchi method was originally used in many manufacturing industries, but lately has been widely used in other sectors such as services, accounting, insurance and financial services. By using a 30% tolerance on KLBFâs PBV and ROA ratio, then the loss function was calculated to prioritizing selection on LQ45 stocks are AALI, HEXA, INTP, UNTR, SMGR and ASII. Another conclusion of this research was the LQ45 stocks with the highest returns do not always include in prioritizing stock on LQ45 by Taguchi Loss Function. It is found that amongst stocks in prioritizing stock selection on LQ45 only HEXA, UNTR and ASII that can beat return JCI throughout 2010 surpassed. Stocks in prioritizing selection on LQ45 derived from a variety of different sectors from KLBF and also have any market capitalization.